A lithium-rich manganese-based positive electrode material and preparation method thereof and lithium-ion battery
By using a highly active Mn-based capacitant in the preparation process of lithium-rich manganese-based cathode material and co-fired with lithium-rich sintering material, the problem of first-time efficiency reduction under high lithium ratio in the prior art is solved, and the high charging and discharge specific capacity is improved.
Patent Information
- Application Number
- CN202410485628.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-04-22
AI Technical Summary
When the prior art increases the charging specific capacity of lithium-rich manganese-based positive electrode materials, the first efficiency continues to decrease, the discharge specific capacity does not increase significantly, and the consumption of active lithium ions leads to a decrease in capacity.
In the preparation process of lithium-rich manganese-based positive electrode material, a highly active Mn-based volume enhancer is introduced, and co-fired with lithium-rich sintering material, the reaction reduces the residual alkali content on the surface, and forms more Li ion host structures on the surface of the material, absorbing and converting inactive lithium into active lithium.
It is realized that high charging specific capacity is maintained under high lithium ratio conditions, and at the same time, the discharge specific capacity is improved, and a lithium-rich manganese-based positive electrode material with high specific capacity and high first-effect efficiency is prepared.
Smart Images

Figure CN118281295B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a lithium-rich manganese-based positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Lithium-rich manganese-based positive electrode materials, usually expressed as xLi2MnO3·(1-x)LiMO2, where M=one or more of Ni / Co / Mn, have a higher theoretical capacity. The lithium iron phosphate materials and nickel cobalt manganese oxide materials currently used on a large scale in the market have a specific capacity of 140-220mAh / g. Since the positive electrode material is the only source of active lithium ions in the battery system, the energy density of the battery is generally limited to 150-350Wh / kg. Therefore, the development of battery systems above 400Wh / kg and the pursuit of low material costs have made lithium-rich manganese-based materials a focus of attention. Patent CN116040699A discloses a lithium-rich manganese-based precursor, a positive electrode material, a lithium-ion battery and a preparation method thereof. By increasing the molar ratio of LiOH·H2O and the lithium-rich manganese-based precursor, the charge specific capacity is continuously improved, but the first efficiency is continuously reduced, and the discharge specific capacity has not increased significantly. Patent CN110148712B discloses a composite coated modified lithium-rich manganese positive electrode material and a preparation method thereof, which is achieved by filling CO2 gas into a mixture of a base material and deionized water to make the mixture weakly acidic, and slightly acidifying the surface of the base material to promote the full dissolution of residual lithium compounds and free Li on the surface of the base material, thereby improving the initial discharge capacity and efficiency of the material. This method dissolves free active lithium through slightly acidifying treatment, resulting in a decrease in the charge specific capacity.
[0003] Therefore, it is urgent to design a preparation method for lithium-rich manganese-based positive electrode materials to overcome the problem of reduced initial efficiency due to high lithium ratio, while avoiding the phenomenon of active lithium ions being consumed, resulting in reduced capacity. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a lithium-rich manganese-based positive electrode material and a preparation method thereof and a lithium-ion battery. The present invention introduces a highly active Mn-based capacity-increasing agent in the preparation process of the lithium-rich manganese-based positive electrode material, which is co-fired with the lithium-rich sintering material. On the one hand, it can react with the inactive lithium remaining on the surface of the lithium-rich sintering material, reduce the surface residual alkali content, and avoid absorbing H2O and CO2 in the air during the subsequent material processing, causing gel to cause material failure. On the other hand, it can provide more Li ion host structures on the surface of the material, thereby accommodating more lithium ions to be embedded back into the positive electrode lattice structure, absorbing and converting inactive lithium into active lithium that can contribute to capacity, and the capacity-increasing agent is concentrated on the surface, the Li ion transmission path is shorter, the path and impedance of the embedded lithium are reduced, and the activity is higher, which not only ensures the high charge specific capacity of the material under the condition of high lithium ratio, but also improves the discharge specific capacity at the same time, and can obtain a lithium-rich manganese-based positive electrode material with high specific capacity and high initial efficiency.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0007] (1) sintering a mixture containing a Li source, a Mn source, a Ni source and a doping source to obtain a lithium-rich sintered material;
[0008] (2) mixing the lithium-rich sintered material and a Mn-based capacity-enhancing agent, and performing secondary sintering to obtain the lithium-rich manganese-based positive electrode material;
[0009] The metal elements in the Mn source, the Ni source and the doping source are collectively referred to as MT, the molar ratio of the Li element in the Li source to MT is ≥1.2, and the particle size D50 of the Mn-based volume enhancer is ≤3 μm.
[0010] The present invention introduces a highly active Mn-based capacity-enhancing agent during the preparation of the lithium-rich manganese-based positive electrode material. The Mn-based capacity-enhancing agent is co-fired with the lithium-rich sintering material. On the one hand, it can react with the inactive lithium remaining on the surface of the lithium-rich sintering material to reduce the residual alkali content on the surface, and avoid absorbing H2O and CO2 in the air during subsequent material processing to cause gelation and material failure. On the other hand, it can form more Li ion host structures on the surface of the material, thereby accommodating more lithium ions to be back-embedded into the positive electrode lattice structure, absorbing and converting the inactive lithium into active lithium that can contribute to the capacity. The capacity-enhancing agent is concentrated on the surface, the Li ion transmission path is shorter, the path and impedance of the back-embedded lithium are reduced, and the activity is higher, which not only ensures the high charge specific capacity of the material under the condition of high lithium ratio, but also improves the discharge specific capacity. A lithium-rich manganese-based positive electrode material with high specific capacity and high initial efficiency can be prepared.
[0011] In the present invention, the molar ratio of Li element to MT in the Li source is ≥ 1.2, for example, it can be 1.2, 1.5, 2, 2.5 or 5. If the molar ratio of Li element to MT in the Li source is too small, it is difficult to form a lithium-rich material and the capacity is low.
[0012] In the present invention, the particle size D50 of the Mn-based capacity-enhancing agent is ≤3 μm, for example, it can be 3 μm, 2 μm, 1 μm or 0.5 μm, etc. If the particle size D50 of the Mn-based capacity-enhancing agent is too large, it is difficult to adhere to the surface of the lithium-rich sintered material, and thus it cannot fully contact and react with the residual lithium on the surface, and cannot react to generate components with electrochemical activity, and becomes an impurity, thereby reducing the material capacity.
[0013] It should be noted that the present invention does not limit the type of Li source, and illustratively, it may be lithium carbonate or lithium hydroxide.
[0014] It should be noted that the present invention does not limit the types of Mn source and Ni source. For example, they may be nickel manganese hydroxide.
[0015] As a preferred technical solution of the present invention, the doping source includes at least one of an Al source, a B source, a Ca source, a Si source, a Mg source, a Co source, a Ti source, a La source and a Zr source.
[0016] Preferably, the molar ratio of Li element to MT in the Li source is (1.2-2):1, for example, it can be 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, etc., preferably (1.4-1.8):1.
[0017] In the present invention, if the molar ratio of Li element to MT in the Li source is relatively small, that is, the content of MT is too much, a lithium-rich structure cannot be formed and the capacity is low; if the molar ratio of Li element to MT in the Li source is relatively large, that is, the content of Li element is too much, a partial lithium-rich structure will be formed, but other impurities will also be formed. These impurities have no electrochemical activity, so excessive Li content will cause the charge and discharge capacity to drop sharply.
[0018] As a preferred technical solution of the present invention, the mixing method in step (1) includes ball milling.
[0019] Preferably, the Mn source and the Ni source in step (1) are of the same type, for example, manganese nickel hydroxide or nickel cobalt manganese hydroxide.
[0020] As a preferred technical solution of the present invention, the primary sintering in step (1) is carried out in an oxygen-containing atmosphere.
[0021] Preferably, the oxygen-containing atmosphere includes an air atmosphere or an oxygen atmosphere.
[0022] Preferably, the primary sintering temperature in step (1) is 700-1100°C, for example, 700°C, 800°C, 900°C, 1000°C or 1100°C.
[0023] Preferably, the time of the primary sintering in step (1) is 5-30 h, for example, 5 h, 10 h, 15 h, 20 h, 25 h or 30 h.
[0024] As a preferred technical solution of the present invention, the Mn-based volume extracting agent in step (2) includes Mn-based hydroxide and / or Mn-based carbonate.
[0025] Preferably, the Mn-based hydroxide includes nickel-cobalt-manganese hydroxide and / or nickel-manganese hydroxide.
[0026] Preferably, the particle size D50 of the Mn-based volume extracting agent in step (2) is 0.5-3 μm, for example, it can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0027] It should be noted that the particle size D50 of the Mn-based volume enhancer is measured by using the Malvern 3000 equipment with reference to the national standard GB / T19077-2016 Particle Size Distribution Laser Diffraction Method.
[0028] As a preferred technical solution of the present invention, the mass ratio of the Mn-based volume extracting agent to the lithium-rich sintering material in step (2) is (0.05-1):100, for example, it can be 0.05:100, 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100 or 1:100, etc., preferably (0.3-0.7):100.
[0029] In the present invention, if the mass ratio of the Mn-based capacity-enhancing agent to the lithium-rich sintered material is too large, after the residual lithium on the surface and part of the capacity-enhancing agent are completely reacted, a large amount of the capacity-enhancing agent cannot continue to react to generate electrochemically active components due to the lack of raw materials, and becomes impurities, reducing the material capacity.
[0030] As a preferred technical solution of the present invention, the secondary sintering in step (2) is carried out in an oxygen-containing atmosphere.
[0031] Preferably, the temperature of the secondary sintering in step (2) is 400-900°C, for example, it can be 400°C, 500°C, 600°C, 700°C, 800°C or 900°C.
[0032] In the present invention, if the temperature of the secondary sintering is too low, the reaction temperature of the capacity extracting agent and the residual lithium on the surface cannot be reached, the material capacity is reduced, and the efficiency is deteriorated; if the temperature of the secondary sintering is too high, more active lithium on the surface is volatilized, causing the destruction of the structure of the bulk material and reducing the material capacity.
[0033] Preferably, the secondary sintering time in step (2) is 3-15 h, for example, 3 h, 5 h, 7 h, 9 h, 11 h, 13 h or 15 h.
[0034] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0035] (1) ball-milling a Mn source, a Ni source, a Li source and a doping source to obtain a mixed material, and then sintering the mixed material once in an oxygen-containing atmosphere, wherein the temperature of the first sintering is 700-1100° C. and the time of the first sintering is 5-30 hours to obtain a lithium-rich sintered material;
[0036] Wherein, the Mn source and the Ni source are both manganese nickel hydroxide, the metal elements in the Mn source, the Ni source and the doping source are collectively referred to as MT, and the molar ratio of the Li element in the Li source to MT is (1.2-2):1;
[0037] (2) ball-milling the lithium-rich sintered material and a Mn-based capacity-enhancing agent having a particle size D50 of 0.5-3 μm, and performing secondary sintering in an oxygen-containing atmosphere at a temperature of 400-900° C. for 3-15 h to obtain a lithium-rich manganese-based positive electrode material;
[0038] Among them, the mass ratio of the Mn-based capacity-enhancing agent and the lithium-rich sintering material is (0.05-1):100.
[0039] In a second aspect, the present invention provides a lithium-rich manganese-based positive electrode material prepared by the preparation method described in the first aspect, wherein the general formula of the lithium-rich manganese-based positive electrode material is Li 1+x Ni a Mn b M c O2, wherein 0≤x≤0.33, 0≤a≤0.65, 0≤b≤0.7, 0≤c≤0.1, and x+a+b+c=1, and M is a doping element.
[0040] The lithium-rich manganese-based positive electrode material prepared by the preparation method provided by the present invention has excellent first efficiency, as well as high charge specific capacity and discharge specific capacity.
[0041] In the present invention, 0≤x≤0.33, for example, it can be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 or 0.33, 0≤a≤0.65, for example, it can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or 0.65, 0≤b≤0.7, for example, it can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7, 0≤c≤0.1, for example, it can be 0, 0.02, 0.04, 0.06, 0.08 or 0.1, etc.
[0042] Preferably, the particle size D50 of the lithium-rich manganese-based positive electrode material is 3-12 μm, for example, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm or 12 μm.
[0043] It should be noted that the particle size D50 of the lithium-rich manganese-based positive electrode material is measured with reference to the national standard "GB / T19077-2016 Particle Size Distribution Laser Diffraction Method" using the Malvern 3000 equipment.
[0044] In a third aspect, the present invention provides a lithium-ion battery, wherein the positive electrode of the lithium-ion battery comprises the lithium-rich manganese-based positive electrode material as described in the second aspect.
[0045] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention introduces a highly active Mn-based capacity-enhancing agent during the preparation of the lithium-rich manganese-based positive electrode material. The Mn-based capacity-enhancing agent is co-fired with the lithium-rich sintering material. On the one hand, it can react with the inactive lithium remaining on the surface of the lithium-rich sintering material during the secondary sintering process to reduce the residual alkali content on the surface, and avoid absorbing H2O and CO2 in the air during subsequent material processing to cause gelation and material failure. On the other hand, it can form more Li ion host structures on the surface of the material, thereby accommodating more lithium ions to be embedded back into the positive electrode lattice structure, absorbing and converting the inactive lithium into active lithium that can contribute to the capacity. The capacity-enhancing agent is concentrated on the surface, the Li ion transmission path is shorter, the path and impedance of the embedded lithium are reduced, and the activity is higher. This not only ensures the high charge specific capacity of the material under the condition of high lithium ratio, but also improves the discharge specific capacity. A lithium-rich manganese-based positive electrode material with high specific capacity and high initial efficiency can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a SEM image of the Mn-based volume extractor in the preparation method provided in Example 9 of the present invention. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0050] Example 1
[0051] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0052] (1) 100 g of [Ni 0.25 Mn 0.7 Co 0.05 ](OH)2, 64.6g of Li2CO3 and 0.58g of Al2O3 are ball-milled to obtain a mixture, and then the mixture is sintered once in an air atmosphere at a temperature of 900°C for 18h, and a lithium-rich sintered material is obtained after crushing and screening;
[0053] Among them, [Ni 0.25 Mn 0.7 Co 0.05 ](OH)2 and the metal elements in Al2O3 are collectively referred to as MT, and the molar ratio of Li element to MT in Li2CO3 is 1.6:1;
[0054] (2) 100 g of the lithium-rich sintered material and 0.4 g of [Ni 0.25 Mn 0.7 Co 0.05 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an air atmosphere at a temperature of 700°C and a time of 10 hours. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0055] Among them, [Ni 0.25 Mn 0.7 Co 0.05 The mass ratio of ](OH)2 and lithium-rich sintering material is 0.4:100.
[0056] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.23 Ni 0.19 Mn 0.54 Co 0.04 Al 0.008 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 7 μm.
[0057] Example 2
[0058] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0059] (1) 100 g of [Ni 0.05 Mn 0.9 Co 0.05 ](OH)2, 69.6g of Li2CO3 and 0.82g of ZrO2 are ball-milled to obtain a mixture, and then the mixture is sintered once in an air atmosphere at a temperature of 900°C for 15h, and a lithium-rich sintered material is obtained after crushing and screening;
[0060] Among them, [Ni 0.05 Mn 0.9 Co 0.05 The metal elements in ](OH)2 and ZrO2 are collectively referred to as MT, and the molar ratio of Li element to MT in Li2CO3 is 1.7:1;
[0061] (2) 100 g of the lithium-rich sintered material and 0.5 g of [Ni 0.35 Mn 0.65 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an air atmosphere at a temperature of 650°C and a time of 9 hours. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0062] Among them, [Ni 0.35 Mn 0.65 The mass ratio of ](OH)2 and lithium-rich sintering material is 0.5:100.
[0063] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.25 Ni 0.04 Mn 0.66 Co 0.04 Zr 0.011 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 10 μm.
[0064] Example 3
[0065] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0066] (1) 100 g of [Ni 0.2 Mn 0.68 Co 0.12](OH)2, 72.6g of Li2CO3 and 0.77g of CaO are ball-milled to obtain a mixture, and then the mixture is sintered once in an oxygen atmosphere at a temperature of 1000°C for 5 hours, and a lithium-rich sintered material is obtained after crushing and screening;
[0067] Among them, [Ni 0.2 Mn 0.68 Co 0.12 The metal elements in ](OH)2 and CaO are collectively referred to as MT, and the molar ratio of Li element to MT in Li2CO3 is 1.8:1;
[0068] (2) 100 g of the lithium-rich sintered material and 1 g of [Ni 0.45 Mn 0.55 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an air atmosphere at a temperature of 900°C and a time of 7h. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0069] Among them, [Ni 0.45 Mn 0.55 The mass ratio of ](OH)2 and lithium-rich sintering material is 1:100.
[0070] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.28 Ni 0.14 Mn 0.48 Co 0.09 Ca 0.01 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 10 μm.
[0071] Example 4
[0072] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0073] (1) 100 g of [Ni 0.45 Mn 0.55 ](OH)2, 47.9g of Li2CO3 and 0.06g of SiO2 are ball-milled to obtain a mixture, and then the mixture is sintered once in an oxygen atmosphere at a temperature of 800°C for 25h, and a lithium-rich sintered material is obtained after crushing and screening;
[0074] Among them, [Ni 0.45 Mn 0.55 ](OH)2 and the metal elements in SiO2 are collectively referred to as MT, and the molar ratio of Li element and MT in Li2CO3 is 1.2:1;
[0075] (2) 100 g of the lithium-rich sintered material and 0.05 g of [Ni 0.35 Mn 0.65 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an oxygen atmosphere at a temperature of 850°C and a time of 15h. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0076] Among them, [Ni 0.35 Mn 0.65 The mass ratio of ](OH)2 and lithium-rich sintering material is 0.05:100.
[0077] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.09 Ni 0.41 Mn 0.5 Si 0.001 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 12 μm.
[0078] Example 5
[0079] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0080] (1) 100 g of [Ni 0.9 Mn 0.1 ](OH)2, 73.7g of Li2CO3 and 0.21g of La2O3 are ball-milled to obtain a mixture, and then the mixture is sintered once in an air atmosphere at a sintering temperature of 1100°C for 30h, and a lithium-rich sintered material is obtained after crushing and screening;
[0081] Among them, [Ni 0.9 Mn 0.1 The metal elements in ](OH)2 and La2O3 are collectively referred to as MT, and the molar ratio of Li element to MT in Li2CO3 is 1.9:1;
[0082] (2) 100 g of the lithium-rich sintered material and 0.7 g of [Ni 0.35 Mn 0.65 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an oxygen atmosphere at a temperature of 400°C and a time of 15h. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0083] Among them, [Ni 0.35 Mn 0.65The mass ratio of ](OH)2 and lithium-rich sintering material is 0.7:100.
[0084] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.31 Ni 0.62 Mn 0.07 La 0.003 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 3 μm.
[0085] Example 6
[0086] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0087] (1) 100 g of [Ni 0.35 Mn 0.65 ](OH)2, 77.3g of LiOH·H2O, 0.1g of TiO2 and 0.2g of B2O3 are ball-milled to obtain a mixture, and then the mixture is sintered once in an air atmosphere at a temperature of 950°C for 20h, and a lithium-rich sintered material is obtained after crushing and screening;
[0088] Among them, [Ni 0.35 Mn 0.65 The metal elements in ](OH)2, TiO2 and B2O3 are collectively referred to as MT, and the molar ratio of Li element to MT in LiOH·H2O is 1.7:1;
[0089] (2) 100 g of the lithium-rich sintered material and 0.3 g of [Ni 0.35 Mn 0.65 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an air atmosphere at a temperature of 800°C and a time of 15h. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0090] Among them, [Ni 0.35 Mn 0.65 The mass ratio of ](OH)2 and lithium-rich sintering material is 0.3:100.
[0091] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.26 Ni 0.26 Mn 0.48 Ti 0.001 B 0.001 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 3 μm.
[0092] Example 7
[0093] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0094] (1) 100 g of [Ni 0.3 Mn 0.7 ](OH)2, 52.5g of Li2CO3 and 0.5g of MgO are ball-milled to obtain a mixture, and then the mixture is sintered once in an air atmosphere at a temperature of 980°C for 30h, and a lithium-rich sintered material is obtained after crushing and screening;
[0095] Among them, [Ni 0.3 Mn 0.7 ](OH)2 and the metal elements in MgO are collectively referred to as MT, and the molar ratio of Li element and MT in Li2CO3 is 1.3:1;
[0096] (2) 100 g of the lithium-rich sintered material and 0.3 g of [Ni 0.3 Mn 0.7 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an air atmosphere at a temperature of 900°C and a time of 12h. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0097] Among them, [Ni 0.3 Mn 0.7 The mass ratio of ](OH)2 and lithium-rich sintered material is 0.8:100.
[0098] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.13 Ni 0.26 Mn 0.61 Mg 0.008 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 7 μm.
[0099] Example 8
[0100] The difference between this embodiment and embodiment 7 is that the molar ratio of Li element to MT in Li2CO3 is 1.5:1.
[0101] The rest of the preparation methods and parameters were the same as those in Example 7.
[0102] Example 9
[0103] This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material, the preparation method comprising the following steps:
[0104] (1) 100 g of [Ni 0.3 Mn 0.7 ](OH)2, 68.6g of Li2CO3 and 0.5g of MgO are ball-milled to obtain a mixture, and then the mixture is sintered once in an air atmosphere at a temperature of 980°C for 30h, and a lithium-rich sintered material is obtained after crushing and screening;
[0105] Among them, [Ni 0.3 Mn 0.7 ](OH)2 and the metal elements in MgO are collectively referred to as MT, and the molar ratio of Li element and MT in Li2CO3 is 1.7:1;
[0106] (2) 100 g of the lithium-rich sintered material and 0.3 g of [Ni 0.3 Mn 0.7 ](OH)2 was ball-milled and mixed, and secondary sintering was performed in an air atmosphere at a temperature of 900°C and a time of 12h. After crushing and screening, a lithium-rich manganese-based positive electrode material was obtained;
[0107] Among them, [Ni 0.3 Mn 0.7 The mass ratio of ](OH)2 and lithium-rich sintered material is 0.8:100.
[0108] This embodiment also provides a lithium-rich manganese-based positive electrode material prepared by the above preparation method. The general formula of the lithium-rich manganese-based positive electrode material is Li 1.26 Ni 0.22 Mn 0.52 Mg 0.007 O2, the particle size D50 of the lithium-rich manganese-based positive electrode material is 7 μm.
[0109] Figure 1 The SEM image of the Mn-based volume extracting agent in the preparation method provided in this embodiment is shown. It can be seen from the figure that the Mn-based volume extracting agent [Ni 0.3 Mn 0.7 ]The particle size D50 of (OH)2 is 0.8 μm.
[0110] Example 10
[0111] The difference between this embodiment and embodiment 7 is that the molar ratio of Li element to MT in Li2CO3 is 1.9:1.
[0112] The rest of the preparation methods and parameters were the same as those in Example 7.
[0113] Embodiment 11
[0114] The difference between this embodiment and embodiment 1 is that the molar ratio of Li element to MT in Li2CO3 is 1.1:1.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Example 12
[0117] The difference between this embodiment and embodiment 1 is that the molar ratio of Li element to MT in Li2CO3 is 2.5:1.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Embodiment 13
[0120] The difference between this embodiment and embodiment 9 is that in step (2), [Ni 0.3 Mn 0.7 The mass ratio of ](OH)2 and lithium-rich sintering material is 2:100.
[0121] The rest of the preparation methods and parameters were the same as those in Example 9.
[0122] Embodiment 14
[0123] The difference between this embodiment and embodiment 9 is that the temperature of the secondary sintering in step (2) is 300°C.
[0124] The rest of the preparation methods and parameters were the same as those in Example 9.
[0125] Embodiment 15
[0126] The difference between this embodiment and embodiment 9 is that the temperature of the secondary sintering in step (2) is 1000°C.
[0127] The rest of the preparation methods and parameters were the same as those in Example 9.
[0128] Comparative Example 1
[0129] The difference between this comparative example and Example 9 is that in step (2), no [Ni 0.3 Mn 0.7 ](OH)2 is used as a Mn-based content enhancer.
[0130] The rest of the preparation methods and parameters were the same as those in Example 9.
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 9 is that in step (2), [Ni 0.3 Mn 0.7 ]The particle size D50 of (OH)2 is 4 μm.
[0133] The rest of the preparation methods and parameters were the same as those in Example 9.
[0134] Comparative Example 3
[0135] The difference between this comparative example and Example 9 is that the molar ratio of Li element to MT in Li2CO3 is 1:1.
[0136] The rest of the preparation methods and parameters were the same as those in Example 9.
[0137] Performance Testing
[0138] The lithium-rich manganese-based positive electrode materials prepared based on the above-mentioned embodiments and comparative examples were used to make CR2032 button batteries, and the electrochemical performance tests were carried out.
[0139] The preparation steps of CR2032 button battery include:
[0140] ① Add lithium-rich manganese-based positive electrode material, PVDF (polyvinylidene fluoride) and conductive carbon black into NMP (N-methylpyrrolidone) at a mass ratio of 90:5:5 to prepare a positive electrode slurry, which is then coated on an aluminum foil with a thickness of 12 μm, and then placed in an oven at 120°C for 12 hours to obtain a positive electrode sheet;
[0141] ② In a glove box filled with argon, CR2032 button batteries were used and assembled in the order of negative electrode shell, metal lithium sheet, PE separator, positive electrode sheet, gasket, spring, and positive electrode shell. The electrolyte used was 1 mol / L LiPF6 / (EC+EMC+DMC), and the volume ratio of EC (ethylene carbonate), EMC (ethyl methyl carbonate), and DMC (dimethyl carbonate) in the solvent was 1:1:1.
[0142] Test conditions for electrochemical properties: The battery prepared as above was sealed and left to stand for 24 hours for charge and discharge tests. The charge and discharge voltage range was 2-4.6V. First, it was charged to 4.6V at a constant current rate of 0.1C. Then, it was charged to a current ≤0.05C at a constant voltage of 4.6V and left to stand for 2 minutes. The charge capacity at this time was recorded as C1. Then, it was discharged to 2V at a rate of 0.1C. The discharge capacity at this time was the initial gram capacity, recorded as D1. The first effect E1 = D1 / C1×100%.
[0143] The above test results are shown in Table 1.
[0144] Table 1
[0145]
[0146] analyze:
[0147] As can be seen from the above table, the present invention introduces a highly active Mn-based capacity-extracting agent in the preparation process of the lithium-rich manganese-based positive electrode material. On the one hand, it can react with the inactive lithium remaining on the surface of the lithium-rich sintered material during the secondary sintering process, reduce the residual alkali content on the surface, and avoid absorbing H2O and CO2 in the air during subsequent material processing, causing gelation and material failure. On the other hand, it can form more Li ion host structures on the surface of the material, thereby accommodating more lithium ions to be embedded back into the positive electrode lattice structure, absorbing and converting the inactive lithium into active lithium that can contribute to the capacity. The capacity-extracting agent is concentrated on the surface, and the Li ion transmission path is shorter, which reduces the path and impedance of the embedded lithium and has higher activity. It not only ensures high lithium and high charge specific capacity, but also improves the discharge specific capacity at the same time, thereby obtaining a lithium-rich manganese-based positive electrode material with higher specific capacity and first efficiency.
[0148] It can be seen from Example 1 and Examples 11-12 that if the molar ratio of Li element to MT in Li2CO3 is too small, that is, the content of MT is too high, the lithium-rich Li2MnO3 structure cannot be formed, the discharge capacity is reduced, and the first efficiency is reduced; if the molar ratio of Li element to MT in Li2CO3 is too large, that is, the content of Li element is too high, although a partial lithium-rich structure will be formed, other impurities will also be formed. These impurities have no electrochemical activity, so excessive Li content will lead to reduced charge and discharge capacity and first efficiency.
[0149] It can be seen from Examples 9 and 13 that if [Ni 0.3 Mn 0.7 If the mass ratio of ](OH)2 and lithium-rich sintered material is too large, after the residual lithium on the surface of the lithium-rich sintered material and part of the capacity extractor are completely reacted, a large amount of capacity extractor will still remain and become impurities, causing the charge and discharge capacity and initial efficiency of the positive electrode material to show a downward trend.
[0150] It can be seen from Example 9 and Examples 14-15 that if the temperature of the secondary sintering is too low, the reaction between the capacity extracting agent and the residual lithium on the surface of the lithium-rich sintered material will not be complete, which will lead to a decrease in the material capacity and a significant decrease in efficiency; if the temperature of the secondary sintering is too high, more active lithium on the surface of the lithium-rich sintered material will volatilize, causing damage to the structure of the bulk material, reducing the material capacity, and reducing the primary efficiency.
[0151] It can be seen from Example 9 and Comparative Example 1 that if [Ni 0.3 Mn 0.7 ](OH)2 is used as a Mn-based capacity enhancer. Although the use of a high Li ratio to prepare lithium-rich sintered materials will result in a very high charging capacity, indicating that most of the Li can be released to contribute to the capacity, the Li returned during the discharge process does not have enough host structure to accommodate it, and the surface internal resistance of the superimposed material is large, and it cannot be completely embedded back into the crystal structure, thereby forming residual inactive lithium on the surface, resulting in a decrease in discharge capacity and initial efficiency.
[0152] It can be seen from Example 9 and Comparative Example 2 that if [Ni 0.3 Mn 0.7 If the particle size of ](OH)2 is too large, it will be difficult for the capacity-enhancing agent to adhere to the surface of the lithium-rich sintered material, and it will not be able to fully contact and react with the residual lithium on its surface, and will not be able to react to generate electrochemically active components. Instead, it will become an impurity, significantly reducing the capacity of the material.
[0153] It can be seen from Example 9 and Comparative Example 3 that if the molar ratio of Li element to MT in Li2CO3 is too small, it is difficult to form a lithium-rich material and the capacity is low.
[0154] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a lithium-rich manganese-based positive electrode material, characterized in that: The preparation method comprises the following steps: (1) ball-milling a Mn source, a Ni source, a Li source and a doping source to obtain a mixed material, and then sintering the mixed material once in an oxygen-containing atmosphere at a temperature of 700-1100° C. for 5-30 hours to obtain a lithium-rich sintered material; Wherein, the Mn source and the Ni source are both manganese nickel hydroxide, the metal elements in the Mn source, the Ni source and the doping source are collectively referred to as MT, and the molar ratio of the Li element in the Li source to MT is 1.2-2:1; (2) ball-milling the lithium-rich sintered material and a Mn-based capacity-enhancing agent with a particle size D50 ≤ 3 μm, and performing secondary sintering in an oxygen-containing atmosphere at a temperature of 400-900° C. for a time of 3-15 h to obtain a lithium-rich manganese-based positive electrode material; The Mn-based volume extracting agent is a Mn-based hydroxide and / or a Mn-based carbonate; the Mn-based hydroxide is a nickel-cobalt-manganese hydroxide and / or a nickel-manganese hydroxide; Among them, the mass ratio of the Mn-based capacity-enhancing agent to the lithium-rich sintering material is 0.3-1:
100.
2. The preparation method according to claim 1, characterized in that: The doping source includes at least one of an Al source, a B source, a Ca source, a Si source, a Mg source, a Co source, a Ti source, a La source, and a Zr source.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the Li element in the Li source to MT is 1.4-1.8:
1.
4. The preparation method according to claim 1, characterized in that: The Mn source and Ni source in step (1) are of the same type.
5. The preparation method according to claim 1, characterized in that: The particle size D50 of the Mn-based volume extracting agent in step (2) is 0.5-3 μm.
6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the Mn-based volume extracting agent to the lithium-rich sintering material is 0.3-0.7:
100.
7. A lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The general formula of the lithium-rich manganese-based positive electrode material is Li 1+x Ni a Mn b M c O2, wherein 0≤x≤0.33, 0≤a≤0.65, 0≤b≤0.7, 0≤c≤0.1, and x+a+b+c=1, and M is a doping element.
8. The lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: The particle size D50 of the lithium-rich manganese-based positive electrode material is 3-12 μm.
9. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery includes the lithium-rich manganese-based positive electrode material as claimed in claim 7 or 8.
Citation Information
Patent Citations
A composite-coated modified lithium-rich manganese cathode material and its preparation method
CN110148712B
Lithium-rich manganese-based precursor, positive electrode material, lithium ion battery and preparation method of lithium-rich manganese-based precursor
CN116040699A
Preparation method of lithium-rich manganese-based positive electrode material
CN115676910A
Preparation method for double-layer coated lithium-sodium composite lithium-rich manganese-based positive electrode material
WO2024037261A1